Histologic study of use of microfibrillar collagen hemostat in rat dental sockets - Magro-Érnica Natasha; Magro-Filho Osvaldo; Rangel-Garcia Idelmo (Fundação Odontológica de Ribeirão Preto, 2003)
The aim of this paper was to evaluate if the placement of microfibrillar collagen hemostat (MCH) into a dental socket interfered with healing. General anesthesia was administered to 30 adult male Albinus Wistar rats and the maxillary right central incisor was extracted. In the control group after each tooth was extracted, the socket was sutured. In the MCH group after each tooth was extracted, MCH was placed into the socket before suturing. Postoperatively, 5 animals were sacrificed from each group at 7, 21 and 28 days. The right maxilla was removed from each animal and histologic slides were stained with Masson's trichromic and hematoxylin and eosin. Quantitative and qualitative analyses were done. The percentage of bone area in the dental socket was quantified using the Image Lab 98 image analysis system. The bone area formation for the control and MCH groups was: 8.1% and 3.3% at 7 days, 34.4% and 33% at 21 days and 41% and 41.3% at 28 days, respectively. We concluded that MCH interferes with the beginning of dental socket healing but does not interfere with the final healing of the dental socket.